Ларец мудреца: повесть о славном баснописце - первом народном писателе Иване Андреевиче Крылове / В. М. Иванов - Иванов Владимир Михайлович (Лениздат, 1973)
Экземпляры: РБ (20211011) / Инвентарный номер: 30277 / Цена: 4.00 / Авт.знак: И 20 / ББК: 83.3(2Рос=Рус)1